STRATEGI PENINGKATAN KETAHANAN EKONOMI PEREMPUAN KEPALA KELUARGA MASA PEMULIHAN EKONOMI (STUDI KASUS SERIKAT PEKKA ASAHAN) - Sakti Andiyanto; Muhammad Syukri Albani Nasution; Rahmi Syahriza (Research Institute and Community Engagement of UIN MADURA, 2025)
The purpose of this study was to obtain alternative strategies for family economic resilience in the PEKKA Asahan union, and reviewed with maqashid sharia. The method in this study used a qualitative approach with SWOT analysis and QSPM analysis. This study used questionnaires and interviews with 10 respondents divided into 5 SWOT respondents and 5 QSPM respondents. Based on the results of the IFE and EFE calculations, the position for the SWOT analysis can be determined, namely in quadrant I (positive - Positive), namely Aggressive Strategy. An aggressive strategy is a strategy that utilizes the internal strengths of the PEKKA Asahan Regency economic resilience program to seize existing external opportunities. This strategy is also known as the SO (Strengths-Opportunities) strategy. The QSPM matrix is ​​generated from the SWOT matrix contained in the SO strategy. Alternative strategies that are sorted from the highest total attractiveness value are the PEKKA Asahan union business group can utilize digital technology in product marketing, utilize the PEKKA union network to help create wider market potential opportunities, increase collaboration with international organizations and the government to support activities to increase family economic resilience and access to business capital. The role of women as heads of families has a very important contribution in increasing the economic resilience of families and is in line with the principles of maqashid sharia which include five main objectives, namely maintaining religion (hifdz al-din), reason (hifdz al-aql), soul (hifdz al-nafs), descendants (hifdz al-nasl), and property (hifdz al-mal).